Mixed-Dimensional Nanowires/Nanosheet Heterojunction of GaSb/Bi2O2Se for Self-Powered Near-Infrared Photodetection and Photocommunication - Wang, Guangcan; Sa, Zixu; Zang, Zeqi; Li, Pengsheng; Wang, Mingxu; Yang, Bowen; Wang, Xiaoyue; Yin, Yanxue; Yang, Zai‑xing (Nano-Micro Letters, 2025)
With high surface-to-volume ratio, the abundant surface states and high carrier concentration are challenging the near-infrared photodetection behaviors of narrow band gap semiconductors nanowires. In this study, the narrow band gap semiconductor of Bi2O2Se nanosheets (NSs) is adopted to construct mixed-dimensional heterojunctions with GaSb nanowires (NWs) for demonstrating the impressive self-powered NIR photodetection. Benefiting from the built-in electric field of 140 meV, the as-constructed NW/NS mixed-dimensional heterojunction self-powered photodetector shows the low dark current of 0.07 pA, high Ilight/Idark ratio of 82 and fast response times of < 2/2 ms at room temperature. The self-powered photodetector performance can be further enhanced by fabricating the NW array/NS mixed-dimensional heterojunction by using a contact printing technique. The excellent photodetection performance promises the as-constructed NW/NS mixed-dimensional heterojunction self-powered photodetector in imaging and photocommunication. Highlights: 1 The mixed-dimensional type II heterojunction of GaSb nanowires (NWs) and Bi2O2Se nanosheets (NSs) with a built-in electric field of 140 meV is successfully constructed. 2 As-fabricated NW/NS and NW array/NS mixed-dimensional heterojunction photodetectors exhibit as-expected high-performance self-powered photodetection behaviors, including ultralow Idark (0.07 and 0.08 pA), superior Ilight/Idark ratios (82 and 182) and ultrafast photoresponse (< 2/2 and 6/4 ms). 3 As-fabricated NW array/NS mixed-dimensional heterojunction self-powered photodetector promises the future imaging and photocommunication.